Konseling Eksistensial Teknik Strenght Bombardment untuk Menunmbuhkan Kebermaknaan pada Pasien Skizofrenia Paranoid - Ahmad Chalifar Hikmawan; Herlan Pratikto (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2021)
Schizophrenia is a psychotic disorder characterized by disturbed thoughts, emotions, and behavior-thoughts. Schizophrenia can be caused by heredity, psychosocial problems, and family problems. This research is qualitative research and uses a case study approach. This study aims to provide intervention to schizophrenic patients. The results of observations, interviews, and psychological tests showed that the subjects experienced auditory hallucinations and hallucinations in the form of feelings of sick limbs. In addition, the subject also experienced the feeling of being chased. Based on the symptoms that appear, it can be concluded that the subject meets the criteria for the diagnosis of Paranoid Schizophrenia. Based on the results of the assessment obtained, the researcher provided an intervention in the form of existential counseling with strength bombardment techniques with the aim of fostering meaning and self-development of the subject towards better growth. The intervention was carried out for 6 days. The results showed that existential counseling with the strength bombardment technique was effectively used as a medium to cultivate meaning in the subject. After the intervention process was carried out, subject felt that he had the potential and was able to get through the difficult times he had gone through. Keywords: existential counseling; strength bombardment; schizophrenia paranoid.